A single freeze cycle redirects iron mineral transformation - Tao Luo; Tao Chen; Tra My Bui Thi; James Behan; Crispin Hetherington; Khalil Hanna; Jean-François Boily (Science, 2026)
Polycrystalline ice formation concentrates mineral nanoparticles into liquid boundaries between growing ice crystals. Here we show that minutes of freezing dictate iron mineral fate over subsequent months of aqueous aging. A single freeze–thaw cycle irreversibly aggregates ferrihydrite through converging physical and chemical mechanisms. Freeze concentration collapses electrostatic barriers while cryosuction strips hydration layers and compresses nanoparticles into micrometer-scale planar aggregates. Chemical evidence points to interfacial (hydr)oxo bridging, alongside hydrogen bonding, that resists disaggregation. These mechanisms lock nanoparticles into mesocrystal-like assemblages that retain their nanoscale identity but inhibit dissolution–reprecipitation to goethite, instead favoring solid-state transformation to hematite. Ice formation thus acts as a geochemical reactor, driving aggregation and interfacial bonding that redirect iron speciation, with broad implications for nutrient cycling and carbon preservation across the cryosphere.